BIOMASS AND CARBON STOCK ESTIMATION INVENTORY OF INDONESIAN BANANAS (Musa spp.) AND ITS POTENTIAL ROLE FOR LAND REHABILITATION - Setyawan Agung Danarto; Lia Hapsari (SEAMEO BIOTROP, 2015)
Bananas (Musa spp.) are widely cultivated in Indonesia. They are commonly grown in backyards, home gardens, intercropped with short-term crops, and in agroforestry systems. The potential of bananas to sequester carbon has been reported, but information on performance variation among cultivars remains limited. An inventory of biomass and carbon stock (C-stock) estimation was conducted on banana accessions in the Musa germplasm collection of Purwodadi Botanic Garden, Pasuruan. Biomass and C-stock estimations were carried out for 42 individual banana accessions consisting of five wild species and 37 cultivars using a non-destructive allometric equation method for banana. The objectives of this study were to estimate the biomass and C-stock of Indonesian bananas in the Purwodadi germplasm collection, to project time-average above-ground C-stock of banana-based farming systems in Indonesia, and to discuss the role of bananas in landscape rehabilitation. The results showed that biomass and C-stock values varied among accessions. Wild banana species Musa balbisiana had higher biomass and C-stock compared to Musa acuminata. Cultivars containing one or two “B” genomes (ABB and AAB) were more vigorous and contributed higher biomass and C-stock than AAA and AA cultivars. Among the cultivars, the highest C-stock contribution was recorded in Pisang Kepok Bung (average 6.92 kg C/plant), while the lowest was found in Pisang Rayap (average 0.67 kg C/plant). On average, the Indonesian bananas examined contributed approximately 2.26 kg C/plant or 0.98 tonnes C/ha. The total banana growing area increased from 73,539 ha in 2000 to 101,822 ha in 2010 and slightly decreased to 100,600 ha in 2014. These areas contributed an estimated C-stock of 72.28 tonnes (2000), increasing to 100.07 tonnes (2010), followed by a slight decline to 98.97 tonnes in 2014—values based only on recorded cultivation areas. Banana plants—especially when combined with woody tree crops—have potential as key components of agroforestry and mixed farming systems, home gardens, and landscape rehabilitation, contributing to carbon reduction and providing economic benefits for surrounding communities.